2022
DOI: 10.1111/jbi.14393
|View full text |Cite
|
Sign up to set email alerts
|

Moths and butterflies on alien shores: Global biogeography of non‐native Lepidoptera

Abstract: Aim Lepidoptera is a highly diverse, predominantly herbivorous insect order, with species transported to outside their native range largely facilitated by the global trade of plants and plant‐based goods. Analogous to island disharmony, we examine invasion disharmony, where species filtering during invasions increases systematic compositional differences between native and non‐native species assemblages, and test whether some families are more successful at establishing in non‐native regions than others. Locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…Variation among herbivore species in the extent of both their intra-and intercontinental invasion success most likely coincides with the phenomenon of 'invasion disharmony', where certain groups of insects are over-represented among non-natives, while others are under-represented. This phenomenon has previously been demonstrated for worldwide Coleoptera (Liebhold et al, 2021) and Lepidoptera (Mally et al, 2022) invasions. Among the North American native Robinia specialists, Megacyllene robiniae has spread the furthest beyond the black locust native range in the Nearctic, while it has not spread to any other biogeographic region.…”
Section: Discussionsupporting
confidence: 61%
“…Variation among herbivore species in the extent of both their intra-and intercontinental invasion success most likely coincides with the phenomenon of 'invasion disharmony', where certain groups of insects are over-represented among non-natives, while others are under-represented. This phenomenon has previously been demonstrated for worldwide Coleoptera (Liebhold et al, 2021) and Lepidoptera (Mally et al, 2022) invasions. Among the North American native Robinia specialists, Megacyllene robiniae has spread the furthest beyond the black locust native range in the Nearctic, while it has not spread to any other biogeographic region.…”
Section: Discussionsupporting
confidence: 61%
“…Conversely, there can be various reasons why species may not spread into suitable areas. For instance, lepidopterous species from the Geometridae, including M. privata studied in this research, are not extensively represented among invasive species, and macromoths are underrepresented in pest establishments (Mally et al, 2022). On the other hand, species with continuous development are more likely to become invasive compared to species with diapause, which is the case with M. privata , P. atomaria , P. beata and P. cloelia (Carne, 1996; Steinbauer et al, 2004b; Yamoah et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We found that Hemiptera are under-represented on risk lists compared with establishments, while cerambycid beetles and Lepidoptera are considered more of a risk to forestry than they have proven historically. Australia has very high diversity among native fauna of Lepidoptera, and among the lowest ratio of non-native to native Lepidoptera species in the world [38]. This apparent lower establishment rate may, in part, be driven by competitive exclusion (e.g.…”
Section: Discussionmentioning
confidence: 99%